Pengaruh Entrepreneurial Self Efficiacy Dan Opportunity Recognition Terhadap Entrepreneurial Intention Dengan Entrepreneurialship Education Sebagai Variabel Moderating (Studi Kasus SMAN 1 Pantai Cermin) - Nadhilla Sari; Hani Maisyarah Batubara; Yelnita Yelnita; Kristiana Astuti; Kendis Anwar; Susi Evanita (Departement of Mathematics Education, 2023)
This study aims to determine the effect of entrepreneurial self-efficacy and opportunity recognition on entrepreneurialship education. The method in this study uses quantitative methods. The population used in this study were all students of SMA N 1 Pantai Cermin. The number of samples in this study was 112 students. The data collection technique used in this study was a questionnaire which was analyzed using Structural Equation Modeling (SEM) with the Smart PLS analysis tool. The results of the analysis show that there is a positive and significant effect of Self efficacy on entrepreneurial intention. There is a positive and significant effect of opportunity recognition on entrepreneurial intention. There is a significant influence of entrepreneurial self-efficacy on entrepreneurial intention through entrepreneurial education. However, there is no effect of opportunity recognition on entrepreneurial intention through entrepreneurial education.